Values from a psychological perspective — theoretical overview - Waszkiewicz, Adrian Andrzej (Hybris, 2016)
The paper attempts to recognize the values from the psychological perspective. It focuses on the description of this multifaceted concepts and attempts to define and operationalize the values ​​and their systems together with hierarchies and indicate their impact on individuals and society. Paper tends to subjective analysis and individual approach to values. It describes their meaning and importance for the proper human mental development and their impact on achieving optimal well-being. Paper presents theories of value in conceptualization of Scheler, Rokeach, Kluckhohn and Schwartz and attempts to identify integrative approach and the application of the values theory in axiotherapy.